2003
DOI: 10.1590/s1516-31802003000100008
|View full text |Cite
|
Sign up to set email alerts
|

Crying as a precipitating factor for migraine and tension-type headache

Abstract: The physiology of crying is not well documented or understood. The act of crying seems to be an important precipitating factor for primary headaches and it should be studied further. The authors welcome comments on the matter and would like to work in collaboration with other groups interested in this subject.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 2 publications
1
6
0
4
Order By: Relevance
“…Many studies have reported that migraine headaches started or worsened with consuming coffee, chocolate, and cheese. 19,27 In our study there was no difference between alcohol, cheese, chocolate, coffee, soda consuming and prevalence of probable migraine. We conducted the questionnaire to individuals based on their expressions therefore it might obscured the real relationship between consume tendency and migraine.…”
Section: Discussionmentioning
confidence: 42%
“…Many studies have reported that migraine headaches started or worsened with consuming coffee, chocolate, and cheese. 19,27 In our study there was no difference between alcohol, cheese, chocolate, coffee, soda consuming and prevalence of probable migraine. We conducted the questionnaire to individuals based on their expressions therefore it might obscured the real relationship between consume tendency and migraine.…”
Section: Discussionmentioning
confidence: 42%
“…Fatores desencadeantes incluem, mas não se limitam a, mudanças dietéticas, déficit de hidratação, tensão elevada da musculatura da cabeça, pescoço e ombros, posições/postura inadequadas, ciclo menstrual, distúrbios do sono ou excesso dele, bruxismo, atividade mastigatória, consumo de determinados alimentos, bem como exposição a luz, odores fortes e barulhos 4,21,22 . Embora a relação causa-efeito não esteja totalmente esclarecida, fatores emocionais -tais como estresse, ansiedade e depressão -são o gatilho principal da CTT, em especial quando ocorrem de forma prolongada 4,22 .…”
Section: Fatores Desencadeantesunclassified
“…Embora a relação causa-efeito não esteja totalmente esclarecida, fatores emocionais -tais como estresse, ansiedade e depressão -são o gatilho principal da CTT, em especial quando ocorrem de forma prolongada 4,22 . Alterações climáticas com quedas bruscas de temperatura são cogitadas como possíveis causas da cefaleia tensional, devido ao aumento generalizado da tensão muscular resultante das baixas temperaturas, associado a uma menor ingestão hídrica, comum em períodos mais frios 4,21,22 . O consumo abusivo de determinadas substancias também pode desencadear a CTT: cafeína, por se tratar de uma substancia estimulante do Sistema Nervoso Central e desidratante; assim como analgésicos, tabaco e álcool 4,22 .…”
Section: Fatores Desencadeantesunclassified
See 1 more Smart Citation
“…Some Brazilian members of the IHS initiated their specialization in centers outside Brazil. Carlos A. Bordini, Maurice Vincent, Yára Dadalti Fragoso, and Deusvenir de Souza Carvalho spent some time during their training in Trondheim University Hospital, Trondheim, Norway, and a series of articles were published in collaboration with Ottar Sjaastad . We will mention a few other Brazilians and the IHS member under whose supervision they studied or worked with: Luiz Paulo Queiroz/Alan M. Rapoport; Fernando Kowacs/Peter Goadsby; Mario Peres/Stephen Silberstein.…”
Section: International Relationshipmentioning
confidence: 99%